2016
DOI: 10.1364/oe.24.013033
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear optical properties of multilayer graphene in the infrared

Abstract: A negative value for the nonlinear refraction in graphene is experimentally observed and unambiguously verified by performing a theoretical analysis arising from the conductivity of the graphene monolayer. The nonlinear optical properties of multi-layer graphene are experimentally studied by employing the Z-scan technique. The measurements are carried out at 1150, 1550, 1900 and 2400 nm with a 100-femtosecond laser source. Under laser illumination the multi-layer graphene exhibits a transmittance increase due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
60
1
12

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(84 citation statements)
references
References 42 publications
9
60
1
12
Order By: Relevance
“…In conclusion, we have evaluated the nonlinear coefficients of GSWs through the coincidence measurement of the photon-pair generation via SFWM. According to the theoretical analysis using the coupled-wave equations [38][39][40][41], our results clearly reflected a six to tenfold graphene-induced optical NLE, which is consistent with previously reported values [5,11,12,16,22,23,25]. Because unwanted effects (e.g.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In conclusion, we have evaluated the nonlinear coefficients of GSWs through the coincidence measurement of the photon-pair generation via SFWM. According to the theoretical analysis using the coupled-wave equations [38][39][40][41], our results clearly reflected a six to tenfold graphene-induced optical NLE, which is consistent with previously reported values [5,11,12,16,22,23,25]. Because unwanted effects (e.g.…”
Section: Resultssupporting
confidence: 92%
“…There are large discrepancies between the reported values of the third-order nonlinear coefficient of graphene. For example, the experimentally obtained effective nonlinear refractive index n 2,eff of graphene ranges from 10 −11 -10 −13 m 2 /W for stimulated four-wave mixing (FWM) [5,[11][12][13]17] or optical Kerr effect (OKE) [16,[18][19][20][21][22][23][24][25] to 10 −15 -10 −17 m 2 /W for third-harmonic generation (THG) [14,15]. Not only the absolute value, but also the positive/negative sign of the effective nonlinear refractive index n 2,eff of graphene has been under active investigation [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…The thirdorder nonlinear optical response of graphene has been investigated by many groups, theoretically [2][3][4][5][6][7][8] , and experimentally [9][10][11][12][13][14][15] . More recently, other 2D materials have also been studied 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, while early experimental investigations did not explicitly distinguish between the signs of graphene's nonlinear coefficient, very recent works have unanimously found negative nonlinear refractive indices in the visible and telecommunication wavelengths. Three independent works in 2016, published during June, July and August, respectively, verified the negative index of refraction for graphene [112][113][114]. Demetriou et al [112] measured n 2 to be of the order of −10 −13 m 2 W −1 at wavelengths between 1150 and 2400 nm with a 100 fs source using the Z-scan technique.…”
Section: (C) Negative Nonlinear Refractive Index Of Graphenementioning
confidence: 94%
“…Three independent works in 2016, published during June, July and August, respectively, verified the negative index of refraction for graphene [112][113][114]. Demetriou et al [112] measured n 2 to be of the order of −10 −13 m 2 W −1 at wavelengths between 1150 and 2400 nm with a 100 fs source using the Z-scan technique. Dremetsika et al [113] also found n 2 to be −1.1 × 10 −13 m 2 W −1 using the optically heterodyne-detected optical Kerr effect (OHD-OKE), as shown in figure 11b, using a 1600 nm Ti : sapphire laser with 180 fs pulses, concurring with the previous Z-scan measurements.…”
Section: (C) Negative Nonlinear Refractive Index Of Graphenementioning
confidence: 94%